Metabolic complications and clinical outcomes of non-functioning adrenal incidentalomas: a systematic review and meta-analysis - Xiaolan Li; Huiyu Lan; Xinying Lin; Huibin Huang; Junping Wen; Gang Chen; Wei Lin (BMC Endocrine Disorders)
Abstract Background Increased detection of non-functioning adrenal incidentalomas (NFAI) due to widespread abdominal imaging may underestimate associated metabolic risks. To examine NFAI's impact on metabolic comorbidities and evaluate outcomes in surgical and non-surgical management, including changes in NFAI characteristics during follow-up. Methods Meta-analysis of studies from PubMed, Embase, Cochrane Library, and Web of Science (January 2000 to May 2024). Studies focusing on patients with serum cortisol levels ≤ 50 nmol/L after 1 mg dexamethasone suppression test (DST). Prevalence of hypertension, diabetes, obesity, and lipid disorders before and after follow-up. Tumor growth (> 10 mm increase) and functional changes (1 mg DST retest) were assessed. Results Eighteen studies met inclusion criteria (n = 2,059). In the non-surgical group, diabetes (RR: 1.33, 95% CI: 1.07–1.65) and lipid disorders (RR: 1.22, 95% CI: 1.07–1.38) increased significantly, while hypertension (RR: 1.07, 95% CI: 0.99–1.16) and obesity (RR: 1.05, 95% CI: 0.91–1.21) showed no significant change. Surgical intervention significantly improved hypertension (RR: 0.67, 95% CI: 0.52–0.86). During mean follow-up of 46.1 months, 4% (95% CI: 2%- 8%) of NFAI enlarged > 10 mm, while 8% (95% CI: 5%- 14%) became functional during 45.1 months of follow-up. Conclusions In patients with NFAI, subtle hormone secretion may exist despite current diagnostic criteria suggesting non-functionality. Such tumors show significant associations with metabolic disorders, particularly diabetes mellitus and dyslipidemia. Future research should focus on developing more sensitive diagnostic methods and establishing evidence-based surgical intervention criteria through prospective studies.